Desarrollo de un negocio que permita la creación de una empresa inmobiliaria y construya el conjunto habitacional Viareggio - Ron Salas, José Luis (2010)
The business plan is based on the creation of an estate called Opermobi, which is created to meet the demand for existing housing and bring something to the housing shortage that currently exists in Ecuador. The primary objective of this company will provide consumers with quality homes and apartments at fair prices. The pilot project is the construction of residential complex viareggio but you want the company to continue with new projects. We did a market research, the main tools: expert interview and survey. The result was that now is a good time to start in this area due to high demand for housing and current government support to this sector, With regard to the financial side financial analysis indicates that in any of the three scenarios: pessimistic, normal, optimistic NPV is positive and the IRR is greater than the discount rate required, so it is concluded that the project profitable. It was found that would be better that the project is undertaken by a party with its own funds and another with a bank loan, because if he does so the yields will be better, this is reflected both in the van as the IRR that are superior to a project without financial leverage. In conclusion, this project was originally conducted with all the seriousness of the case, using real data in order to ensure the accuracy of their results and thus ensuring a successful business. All this in order to create a company that provides products and services of excellent quality and which help contribute to the problem of living and working in Ecuador and become a leader in the city of Quito.